Update of the Management of Cutaneous Squamous-cell Carcinoma - Eve Maubec (Medical Journals Sweden, 2020)
For all primary cutaneous squamous cell carcinomas (cSCCs), physical examination should include full skin examination, recording of tumour diameter and regional lymph-node-basin status. Surgery is the treatment of choice, with a minimal 5-mm margin. For elderly patients with well-differentiated tumours, other surgical modalities can be explored. Surgery for organ-transplant recipients should not be delayed. The issue with cSCC is identifying high-risk tumours with staging, as this may alter treatment and follow-up schedules. Adjuvant radiation therapy should be considered for incomplete resection, when re-excision is impossible or there are poor-prognosis histological findings. Recommendations are biannual dermatological surveillance for at least 2 years, but in elderly patients with small, well-differentiated tumours long-term follow-up is not always necessary. In case of positive lymph nodes, radical dissection is needed, with optional regional postoperative adjuvant radiation. Advanced cSCCs are defined as unresectable local, regional or distant disease requiring systemic treatment. Their only approved treatment is the PD-1 inhibitor, cemiplimab. Trials evaluating adjuvant or neo-adjuvant anti-PD-1 are ongoing. Platin-based chemo or anti-EGFR therapies are possible second-line treatments. For transplant patients, minimizing immunosuppression and switching to sirolimus must be considered at first appearance of cSCC.